Regression of melanocytic nevi on the lines of bending. - Milano, A. (European Journal of Pediatric Dermatology, 2012)
A 6-month-old baby girl was first observed due to the presence of a pigmentary lesion of the left arm. The physical examination revealed a melanocytic nevus of about 2 cm in diameter located on the flexor surface of the left elbow; a clear furrow was present on the line of flexion of the elbow (Fig. 1). The dermoscopic examination (Fig. 2) of the nevus showed a globular pattern and a significant reduction of the globules at the level of the furrow. The final diagnosis was congenital melanocytic nevus with spontaneous regression at the level of joint lines of bending. Case 2. This is a case comparable to the previous one, for the presence of spontaneous regression at the level of abdominal lines of bending in a congenital melanocytic nevus of about 10 cm in diameter (Fig. 3, 4) in a 1-year-old boy.